Analisis Bibliometrik Kompetensi Insinyur Teknik Lingkungan Keahlian Pengelolaan Limbah Padat - Sumarlin, Sumarlin; Sukamta, Sri; Basyrun, Basyrun (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
Research on environmental engineering competencies in solid waste management remains fragmented and primarily focused on technical aspects. This study maps the evolution of this field using a quantitative bibliometric approach. Bibliographic data were retrieved from Google Scholar via Publish or Perish (PoP) using the query "engineering competency" AND "waste management" and covering the period 2016–2026. After screening, 200 articles were retained in the final dataset. The data were analyzed using VOSviewer 1.6.20 through keyword co-occurrence network analysis. The findings reveal a global research convergence around sustainability, waste management, and engineering education, with an increasing focus on Industry 4.0 technologies and the circular economy. The results suggest a shift in engineering competency frameworks from conventional technical skills toward multidisciplinary expertise grounded in green skills and systems thinking to support sustainable development.